Cohousing design guidelines for better social integration in the United Arab Emirates - Yahia, Moohammed Wasim; Mushtaha, Emad; Yassin, Samar Adel; AlFoudari, Kawthar Ahmad; Atoum, Yasmeen Adnan; Opoku, Alex; Dirar, Samir; Maksoud, Aref Mohamad (Frontiers in Built Environment, 2023)
Considering cohousing as a new typology in the United Arab Emirates' housing market is a challenge due to the cultural and societal dimensions. However, the variety of societies in the Emirates reflecting various habits, experiences, and traditions can allow testing such new types of housing which can be adapted to the local context, considering the needs of the society. This study aims at developing design guidelines for future cohousing in the United Arab Emirates (UAE), considering the pillars of Estidama program, i.e., social, cultural, economic, and environmental aspects, in addition to the role of architecture design. The present study is based on an empirical investigation from the viewpoint of future cohousing residents in the UAE. Semi-structured interviews considering 87 individuals were conducted. Moreover, a focus group discussion targeting 8 professionals was performed. Furthermore, the Quality Function Deployment (QFD) method was applied to include the people's voices directly when developing the design guidelines for cohousing in the UAE. The study showed that the aspects of culture and privacy are crucial in the future of cohousing in the UAE. In addition, providing local facilities such as Majles and praying rooms is vital to consider. Moreover, other aspects such as sustainable design, universal design, and safety are also valuable. For the outdoor environment, the study highlighted the importance of urban design quality, landscape solutions, shading, and natural ventilation strategies in outdoor spaces. Future cohousing in the UAE is expected to enhance social interaction and contribute to sustainability in the long-term perspective.